The National Health Insurance and Infant Mortality: A Study from Indonesia - Ridwan Ibadurrohman; Witri Indriyani (Jurnal Ekonomi Pembangunan, 2026)
This study examines the relationship between Indonesia’s National Health Insurance program (Jaminan Kesehatan Nasional/JKN) and infant mortality. Using data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI), the analysis applies Propensity Score Matching (PSM) to address potential selection bias. After controlling for a range of health-related, demographic, and socioeconomic variables, the results show that participation in the National Health Insurance program is positively and significantly associated with higher perinatal survival, indicating lower infant mortality. However, the heterogeneity analysis highlights important distributional differences. A positive, statistically significant association is observed only among households in the low and middle-income groups, suggesting that the benefits of JKN are not evenly distributed across income levels. Moreover, when examined by geographic region, the significant association between JKN utilization and improved perinatal survival is found only in Java and Sumatra. This study provides updated national evidence on the association between JKN utilization and infant mortality using the latest survey data.